The Role of Civil Society and Religious Organizations in Shaping Environmental Policy in Bangladesh - Saha, Labonno (FISIP UIN Sunan Gunung Djati Bandung, 2024)
Research Problem: The intersection of religion, civil society, and public policy is an increasingly relevant area of study, particularly in the context of environmental degradation. In Bangladesh, the impacts of climate change, industrialization, and globalization have created significant environmental challenges. These challenges necessitate a critical examination of the role of civil society, including religious organizations, in addressing environmental issues. The key question is: How effectively is civil society, in conjunction with religious institutions, contributing to the environmental movement and influencing policy reform in Bangladesh? Research purposes: This paper aims to explore the role of civil society, including the influence of religious organizations, in the environmental movement in Bangladesh. It seeks to understand how civil society organizations engage in advocacy, lobbying, stakeholder pressure, environmental impact assessments, and grassroots mobilization. The goal is to evaluate how these efforts shape public policy on environmental governance in a religious and sociopolitical context. Research methods: : This study uses a qualitative, review-based approach, relying on secondary data from existing literature, media reports, and policy documents. It critically examines the involvement of civil society organizations in the environmental movement, with a focus on how religious values and institutions intersect with public policy efforts in Bangladesh’s environmental governance. Results and Discussion: The findings suggest that civil society organizations, including those with religious affiliations, play an important role in influencing environmental policy in Bangladesh. Through advocacy, lobbying, and public mobilization, these organizations have brought attention to critical environmental issues, facilitating public participation in environmental governance. However, challenges remain, including political biases and limited resources, which affect their ability to fully shape policy. Religious organizations have also been shown to contribute moral and ethical dimensions to environmental activism, aligning their values with sustainable development goals. Research Implications and Contributions: The research underscores the importance of integrating religious organizations into the broader framework of civil society engagement in environmental governance. It highlights how religious values can complement public policy efforts, contributing to a more holistic approach to sustainable development. The paper provides recommendations for policymakers to strengthen collaboration between civil society, religious institutions, and government bodies to make environmental policy more effective and inclusive, aligning with the journal’s scope of exploring the intersection of religion and public policy.